Virtual humano, humano virtual: uma abordagem teórica da personagem em mundos virtuais - Corrêa, Luciana Espíndola (2011)
The main approach of this dissertation, entitled Virtual Human, Human Virtual, discuss the applicability of a virtual character's definition, classification and creative process in a conceptual and theoretical perspective. In fact, this perspective proposes to include cyberspace, philosophy, literary criticism and computer design's theories. In order to investigate this possibility, the chapters one and two, of this work, discuss the theoretical basis to propose a virtual characther's definition, classification, creative process's concept. Next, chapters three, four and five develops three cases studies to validate the propositions outlined in previous chapters, addressing different kinds of characters, namely: Ragnarök's Iara, a MMORPG Massively Multiplayer Role Playing Game (RAGNARÖK-BRAZIL, 2010); the night elf's race, of the druid's class, in World of War Craft (WoW), a MMORPG (WOWIIK, 2009); and finally a resident of Second Life virtual environment that intends to imitate all aspects of human life (DAMIANI, 2007) , Liberato Lindman